2017
DOI: 10.3390/ijms18061097
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-Related Protein-9 Ameliorates Ox-LDL-Induced Endothelial Dysfunction via PGC-1α/AMPK-Mediated Antioxidant Enzyme Induction

Abstract: Oxidized low-density lipoprotein (ox-LDL) accumulation is one of the critical determinants in endothelial dysfunction in many cardiovascular diseases such as atherosclerosis. C1q/TNF-related protein 9 (CTRP9) is identified to be an adipocytokine with cardioprotective properties. However, the potential roles of CTRP9 in endothelial function remain largely elusive. In the present study, the effects of CTRP9 on the proliferation, apoptosis, migration, angiogenesis, nitric oxide (NO) production and oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Although the cytotoxic effects of ox-LDL on vascular endothelial cells have been well-established, the exact role of ox-LDL in migratory capacity is still confusing. Sun et al, demonstrated that ox-LDL inhibited the migration of HUVECs by performing Transwell assay, without excluding the proliferation-inhibitory impacts of ox-LDL on the number of the migrated cells [23]. However, the opposite effect of ox-LDL has been reported by Bao et al, in the same cell line [24].…”
Section: Discussionmentioning
confidence: 80%
“…Although the cytotoxic effects of ox-LDL on vascular endothelial cells have been well-established, the exact role of ox-LDL in migratory capacity is still confusing. Sun et al, demonstrated that ox-LDL inhibited the migration of HUVECs by performing Transwell assay, without excluding the proliferation-inhibitory impacts of ox-LDL on the number of the migrated cells [23]. However, the opposite effect of ox-LDL has been reported by Bao et al, in the same cell line [24].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, oxidized low density lipoprotein (Ox‐LDL) and hyperglycemia are crucial risk factors of endothelial dysfunction, both of which have the capacity of inhibiting the production of NO, promoting EC apoptosis, producing reactive oxygen species (ROS) and reducing mitochondria production. CTRP9 could attenuate ox‐LDL‐induced endothelial injury through antioxidant enzymes dependent on peroxisome proliferator activated receptor γ coactivator ‐1α (PGC‐1α) /AMPK activation (Sun, Zhu, Zhou, Cai, & Qiu, ) and may induce mitochondrial biogenesis and protect high glucose induced endothelial oxidative damage via AdipoR1/SIRT1/PGC‐1α signaling pathway (Cheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide is the main vasodilating factor produced by eNOS in vascular endothelium, and it plays a crucial role in the maintenance of vascular homoeostasis and prevention of atherothrombotic events [17]. Furthermore, the expressions of AT1R and eNOS are regulated by AMPK and PGC-1α [18][19][20].…”
Section: Aspirin Treatmentmentioning
confidence: 99%